Corporate Social Responsibility, Company Size And Capital Intensity Affect Tax Avoidance: Corporate Social Responsibility, Company Siza And Capital Intensity Affect Tax Avoidance - Jayanti, Indah; Afandi, Agus (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
Research proves corporate social responsibility, company size and capital intensity affect tax avoidance. Energy sector companies listed on the IDX for the period 2018-2022 with purposive sampling and secondary data. Multiple linear regression data analysis method processed by Eviews 12 software. The results of this study simultaneously corporate social responsibility, company size and capital intensity have a significant effect on tax avoidance. The results of this study partially corporate social responsibility and company size have no significant effect and capital intensity has a significant negative effect on tax avoidance